Experimental failure analysis in polycarbonate sheet deformed by spif. (April 2021) - Rosa-Sainz, A.; Centeno, G.; Silva, M.B.; Vallellano, C.
Abstract: The analysis of polymeric sheet materials deformed by means of incremental sheet forming technologies has recently caught the attention of a number of research groups of the materials forming community. The versatility of the process, which allow manufacturing customised sheet components without the need of dedicated tools or dies, as well as the many advantages of polymers in terms of cost, recycling, material properties or biocompatibility, make its use suitable in many industrial sectors such as the automotive, the aerospace or the biomedical. In this global scenario, this paper presents an overall experimental investigation of polycarbonate sheets deformed by single point incremental forming, aiming the identification of the influence of the main process parameters in the material formability and the resulting mode of failure. The study is carried out in terms of principal strains that are evaluated within the material forming limit diagrams obtained independently by means of Nakajima tests. In order to provide more general conclusions, two different materials thicknesses are considered. The results allow establishing the forming limits of the polymeric sheet material and the failure mechanism in SPIF for each of the cases considered. Three main failure modes are assessed in the experiments: fracture by cracking, twisting and crazing. A general perspective of the influence of the process parameters in formability and the mode of failure is accomplished, pointing out that: (i) low thicknesses and higher step downs favor the appearance of twisting, (ii) most of the typical forming conditions in SPIF lead to failure by fracture in the absence of necking due to crack opening in mode I of fracture mechanics, and (iii) certain forming conditions promoting polymer degradation such as high spindle speeds and the consequent increase of temperature may be able to active mixed modes of failure in spifed polymeric sheets including crazing combined with fracture.